Postgraduate training and job satisfaction in higher technological institutes of Riobamba, Ecuador - Orozco Inca, Edgar Enrique; Guerra Orozco, Sandra Elizabeth; Guerra Bretaña, Rosa Mayelín (Pulso. Revista de educación, 2021)
The aim of the work is to analyze postgraduate training and job satisfaction of teachers at the Isabel de Godín and Juan de Velasco Higher Technological Institutes in Riobamba, Ecuador. A survey was applied to 37 teachers from the institutes under study. Forty three percent of teachers have completed master’s or specialty studies. The impact of postgraduate academic training is manifested in the promotion to academic positions, greater professional and social prestige, as well as greater competencies for teaching, while the competences for research, social bonding and management have only been acquired moderately. The most generalized perception among teachers is that recognition is not obtained in correspondence with the academic level achieved, which limits the manifestation of the potential impacts of postgraduate academic training on teachers’ job satisfaction. The aspects that generate less job satisfaction among teachers, and should constitute priorities to improve human capital management, are related to limited training for teaching and research, as well as insufficient promotion and recognition of professional development.